Sedimentary and diagenetic history of the Aptian–Albian succession in the Bai Hassan oil field, Zagros Basin, northern Iraq - Łuczyński, Piotr; Abbas, Ibrahim M.; Al-Zaidy, Aiad A.H. (Acta Geologica Polonica, 2026)
The Aptian–Albian succession, consisting of the Lower Qamchuqa, Jawan, Upper Sarmord, and Upper Qamchuqa formations, from five boreholes in the Bai Hassan oil field, Zagros Foreland Basin, northern Iraq, has been studied in terms of facies, microfacies, diagenetic processes and sequence stratigraphy. Eight microfacies were identified: lime mudstone, orbitolina wackestone/packstone, orbitolina-miliolid wackestone, peloidal-miliolid-echinoderm packstone/grainstone, bioclast-mollusc-echinoderm wackestone/packstone, laminated evaporite-carbonate mudstone, planktonic foraminifera wackestone/packstone, and argillaceous pelagic lime mudstone. The succession was deposited in five stages characterised by changing facies patterns in a variety of environments, including: restricted shallow marine/lagoonal, shallow open marine, fore-reef, deep open marine and basinal. The studied deposits were subjected to several diagenetic processes, including: micritization, dissolution, recrystallization, cementation, anhydritization, compaction, and dolomitization, taking place in various diagenetic environments: meteoric phreatic, marine phreatic, vadose, mixing, and burial. Development of diagenetic processes was strongly affected by sea-level fluctuations, causing landward or seaward shifts of various diagenetic environments. In general, the succession is characterised by less cementation, constructive dolomitization and moderate porosity, resulting in moderate to good hydrocarbon reservoir properties in its parts represented by highstand stages, and by moderate porosity, resulting in moderate to good reservoir characteristics in its transgressive stages. The shallow environments represented by restricted and shallow open marine facies are typified by high values of porosity due to dissolution and early dolomitization. Therefore, tectonics was not the only factor that controlled the petrophysical properties and the reservoir distribution within the studied succession in the Bai Hassan oil field.